PROGRAM PENGAJARAN KOKURIKULER DALAM MENINGKATKAN KEMAMPUAN EMOTIONAL QUOTIENT (EQ) SISWA DI MTS TAHFIDZ YANBU’UL QUR’AN KUDUS - Yogik Delta Hermawan (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2020)
Emotional Quotient is an ability that should be owned by each student. Because emotional quotient includes a process that tames emotions and directs them to positive things, for that we need a program in the world of education that is able to respond to this. This study describes how the implementation of the co-curricular preparation program in improving the emotional quotient abilities of MTs Tahfidz Yanbu'ul Qur'an Kudus students. This research uses descriptive qualitative method. The data sources were headmaster, deputy head of curriculum, teachers, and students. Meanwhile, secondary data are relevant research books and journals. Collecting data using observation, interviews, and documentation. The results showed that the implementation of a co-curricular program could improve students' EQ skills. This is evident from the fact that students who often participate in this program have a high sense of respect, responsibility, empathy, and high motivation. Meanwhile, students who rarely participate in co-curricular programs tend to be indifferent and have low motivation. Supporting factors for the implementation of the co-curricular program are the competence of quality teachers, facilities and infrastructure, and monitoring from the principal of madrasah. Meanwhile, the inhibiting factors are the lack of teaching staff, implementation time and non-technical factors.